2021
DOI: 10.3390/ijerph182010790
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Differences in Leisure Satisfaction of Leisure Activity Patterns for South Korean Adults

Abstract: The purpose of this study was to analyse differences in leisure satisfaction among leisure activity participants according to the type of activity including differences by gender. The study subjects were 448 adult men and women who were participating in leisure activities in Seoul, Gyeonggi, Chungcheong, and Gangwon-do, Korea. Frequency analysis, confirmatory factor analysis, and latent mean analysis were applied to the data collected from the participants. First, the form, measurement, and intercept uniformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Thus, H4 was partially confirmed, evidencing that mindfulness and psychological capital mediate links between leisure preferences and life satisfaction. These results signify that leisure preferences and life satisfaction are interrelated constructs mediated by psychological variables, as indicated by previous studies [ 17 , 21 , 28 , 45 , 132 , 137 , 141 , 143 , 146 , 147 , 148 , 149 , 150 ]. However, these associations’ details concerning particular leisure preferences require a more grounded approach, preferably including personality traits as predictors [ 96 ] and psychological needs satisfaction [ 134 ] as covariates in further research.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, H4 was partially confirmed, evidencing that mindfulness and psychological capital mediate links between leisure preferences and life satisfaction. These results signify that leisure preferences and life satisfaction are interrelated constructs mediated by psychological variables, as indicated by previous studies [ 17 , 21 , 28 , 45 , 132 , 137 , 141 , 143 , 146 , 147 , 148 , 149 , 150 ]. However, these associations’ details concerning particular leisure preferences require a more grounded approach, preferably including personality traits as predictors [ 96 ] and psychological needs satisfaction [ 134 ] as covariates in further research.…”
Section: Discussionsupporting
confidence: 88%
“…Possibly, the same research in other world regions would generate different results. Comparison of previous studies suggests that leisure research is sensitive to cultural factors [ 150 , 151 , 152 , 153 ]. Thus, the findings should be taken with concern.…”
Section: Limitationsmentioning
confidence: 99%
“…According to Park and Chon ( 2010 ), it is very important to develop different scales for leisure activities and validate these scales. However, it was indicated that many researchers did not investigate the invariance of measurement tools according to demographic variables (e.g., gender, age, marital status), and it was important for researchers to verify these scales before using the scales developed in the field (Ahn & Song, 2021 ). In this respect, the present study aimed to test whether the differences obtained according to gender, marital status, and age were caused by the measurement tool itself using LSS, and it was found that the differences to be obtained did not originate from the bias of the measurement tool.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the literature, it is observed that the interest in measurement invariance studies that test the construct validity of measurement tools and reveal that the measurement tool does not work biasedly has increased (Casanova et al, 2021 ; Lima-Castro et al, 2021 ). Previous studies on the construct validity of LS investigated the measurement invariance of the Life Satisfaction Scale (LSS) according to the gender variable (Ahn & Song, 2021 ). In addition to Ahn and Song’s ( 2021 ) study, in this study, we aimed to test the measurement invariance of the LSS developed by Beard and Ragheb ( 1980 ) according to not only gender but also age and marital status variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation